1969
DOI: 10.1063/1.1658260
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Behavior of Group III and V Implanted Dopants in Silicon

Abstract: The anneal behavior of layers implanted with dopants from column III (B, Al, Ga, and Tl) and column V (As, Sb, and Bi) in silicon substrates has been investigated. The ranges of implant conditions were energy 20–50 keV, dose 1013–1015/cm2, and substrate temperature 23°–500°C. Hall-effect and sheet resistivity measurements were used to determine the effective number of carriers/cm2 (Ns)eff and the effective mobility μeff. Analysis of nonuniform distributions of carrier densities and mobilities on these measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…Angular scans with Rutherford backscattering spectrometry of Biimplanted Si revealed that a fraction of Bi atoms ͑after hot implants or annealed after implantation͒ are slightly displaced from the lattice rows 6 and are electrically inactive. 7,8 Despite these findings, de Souza and Fichtner 8 showed that the electrical activation yield ͑EAY: ratio of sheet carrier concentration to implanted dose͒ of Bi implanted Si ͑100͒ was about 90% after annealing at 600°C. They also showed that the maximum EAY for rapid thermal annealed ͑RTA͒ samples at T ജ 700°C was achieved after the shortest annealing time and reduced from the initial values.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Angular scans with Rutherford backscattering spectrometry of Biimplanted Si revealed that a fraction of Bi atoms ͑after hot implants or annealed after implantation͒ are slightly displaced from the lattice rows 6 and are electrically inactive. 7,8 Despite these findings, de Souza and Fichtner 8 showed that the electrical activation yield ͑EAY: ratio of sheet carrier concentration to implanted dose͒ of Bi implanted Si ͑100͒ was about 90% after annealing at 600°C. They also showed that the maximum EAY for rapid thermal annealed ͑RTA͒ samples at T ജ 700°C was achieved after the shortest annealing time and reduced from the initial values.…”
mentioning
confidence: 93%
“…This was attributed to the degree of amorphization and dynamic annihilation of Si during HT implantation. 7 Sheet resistance of the junctions ͑in LT and RT implants͒ increased with an increasing thermal budget after 700°C ͑30 s͒ due to deactivation and/or precipitation. 7 It is evident that the process window for activation of the junctions lies within T ഛ 700°C in an acceptable annealing time.…”
mentioning
confidence: 98%
“…2(a)), n s and l e represent effective quantities, or weighted averages of the depth-dependent carrier concentration and mobility. 29 The error bars in (b) and (c) are determined by the finite size and placement of the contacts on the cloverleaf van der Pauw structure according to Ref. 30.…”
Section: B Evolution Of Optical Absorption and Electronic Transport mentioning
confidence: 99%
“…These conditions yielded a maximum bismuth concentration of 1.8 × 10 18 cm −3 (above the solubility limit [25]) in the depth of 90 to 150 nm from the surface. The post-implantation annealing, performed at 650 • C for 30 min in an evacuated quartz tube, led to an activation efficiency [7,[26][27][28] below 60%, resulting in the Bi donor concentration less than 1.1 × 10 18 cm −3 (below the metal-insulator transition [29]). This process was designed to maximize the number of D-R pairs, instead of fully activating all the implanted Bi atoms [30].…”
Section: A Samplesmentioning
confidence: 99%